Did Bank Capital Regulation Exacerbate the Subprime Mortgage Crisis? - M. A. Petersen; M. C. Senosi; J. Mukuddem-Petersen; M. P. Mulaudzi; I. M. Schoeman (Discrete Dynamics in Nature and Society)
This contribution is the second in a series of papers on discrete-time modeling of bank capital regulation and its connection with the subprime mortgage crisis (SMC). The latter was caused by, amongst other things, the downturn in the U.S. housing market, risky lending and borrowing practices, inaccurate credit ratings, credit default swap contracts as well as excessive individual and corporate debt levels. The Basel II Capital Accord's primary tenet is that banks should be given more freedom to decide how much risk exposure to permit; a practice brought into question by the SMC. For instance, institutions worldwide have badly misjudged the risk related to investments ranging from subprime mortgage loans to mortgage-backed securities (MBSs). Also, analysts are now questioning whether Basel II has failed by allowing these institutions to provision less capital for subprime mortgage loan losses from highly rated debt, including MBSs. Other unintended consequences of Basel II include the procyclicality of credit ratings and changes in bank lending behavior. Our main objective is to model the dependence of bank credit and capital on the level of macroeconomic activity under Basel I and Basel II as well as its connection with banking behavior for the period before and during the SMC.